Effects of electromagnetic wave on female reproductive physiology in adult sprague dawley rats - Ali Saeed Hammoodi Al-Chalabi
The growing number of mobile phone users around the world has increased the public awareness regarding electromagnetic radiation effects on hypersensitive individuals, such as new-borns and pregnant women, and whether or not this radiation poses a risk to human health. The main objective of the study is to investigate the impact of 1800 MHz GSM-like frequency on the female reproductive system physiology in Sprague-Dawley rats as animal models. A total of 360 female rats were employed in the study. The study was divided into two phases; phase one tested non-pregnant rats and phase two tested pregnant rats (180 rat/ phase), and each phase consists of control and exposure groups according to the experimental design. Whole-body exposure for 1h, 2h/day at average specific absorption rate of 0.974 W/Kg used signal generators with horn antenna. The female rats’ fertility, teratogenicity and certain physiological parameters during postnatal life, oxidative stress, genotoxicity, histopathological changes in ovarian and uterine tissues and evaluation of thermal effect were studied by using thermographic analyses. Samples and data were collected according to the objectives of the study and then statistically analysed by one and two-way ANOVA where P ≤ 0.05. The results showed that RF-EMW induced infertility in non-pregnant animals through impaired folliculogenesis, alteration in sex hormone concentrations and increase cohobation periods of exposed females. In pregnant rats, impaired embryogenesis was reported through reduction of implantation sites, grown-up embryos, malformation, growth restriction and delay in certain growth markers in postnatal foetuses. Furthermore, RF-EMW induced oxidative stress both in non-pregnant and pregnant exposed rats through increasing lipid peroxidation values reduced antioxidant enzyme activity, reduce melatonin and induced gene expression of selected antioxidant enzymes. Genotoxicity evaluation revealed an increase in the level of DNA damage 8-OHdG enzyme in exposed rats. Although there were variations in P53 tumour suppressor biomarker, but it was not significant in both pregnant and non-pregnant exposed rats as compared to the control groups. Micronuclei formation was observed in granulosa and luteal cells of ovarian sections from exposed rats.